AKTUALISASI PENDIDIKAN ISLAM (Suatu Upaya Membangun Paradigma Integral) - Suwadji, Bpk (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2013)
Islamic education, basically considering the orientation of worldlyand hereafter. Islamic education with universal concepts that need tobe developed or actualized in a learning process that pertain to thedevelopment of Islamic education and the philosophical paradigm ofintegrative paradigm-universal, therefore this paper reveals the needfor the actualization of the basic concepts of Islamic education asempowerment of Muslims.